Can more appropriate support and services be provided for people who attend the emergency department frequently? National Health Service staff views. Issue 11 (31st August 2017) - Ablard, Suzanne; Coates, Elizabeth; Cooper, Cindy; Parry, Glenys; Mason, Suzanne M
Abstract : Background: Interventions designed to help Emergency Department (ED) staff manage frequent attenders are labour-intensive and only benefit a small sample of frequent attenders. We aimed to use the in-depth knowledge of health professionals with experience of working with ED frequent attenders to understand the challenges of managing this group of patients and their opinions on providing more appropriate support. Methods: Semi-structured interviews were conducted with medical and nursing ED staff, mental health liaison nurses and general practitioners (GPs). Interviews covered the following: definitions and experiences of treating frequent attenders and thoughts on alternative service provision. Vignettes of frequent attenders were used to elicit discussions on these topics. Thematic analysis of transcribed interviews was undertaken. Results: Twelve health professionals were interviewed. Three groups of frequent attenders were identified: people with long-term physical conditions, mental health problems and health-related anxiety. Underlying reasons for attendance differed between the groups, highlighting the need for targeted interventions. Suggested interventions included improving self-management of long-term physical conditions; creating a 'go-to' place away from the ED for patients experiencing a mental health crisis; increasing the provision of mental health liaison services; and for patients with health-related anxiety, the role of the GP in the patients' care pathway was emphasised, as were the benefits of providing additional training for ED staff to help identify and support this group. Conclusion: Interventions to address frequent attendance should focus on redirection to and liaison with more appropriate services, located on the hospital site or in the community, tailored to each identified patient group.